Вплив військових дій на біорізноманіття: втрата видів та порушення екосистемних зв'язків - Сакун, Антоніна Олегівна; Кутковий, Д. О.; Пащенко, П. С. (Яроче́нко Я. В., 2025)
Biodiversity is the foundation of ecosystem stability, ensuring the balance of natural processes and supporting the life of all organisms. However, military conflicts have a catastrophic impact on flora and fauna, leading to species loss, the destruction of natural habitats, and the disruption of ecosystem connections. It is crucial to study how combat operations alter natural processes and what long-term consequences this has for ecosystems.
Keywords: екосистеми; довкілля; токсичні речовини; водні екосистеми; війна росії з Україною; руйнівний вплив; забруднення; природоохоронні території